Prospective study of the efficacy of PCNL under local anesthesia based on the ERAS concept - Zhaorong Liu; Zhaorong Liu; Longfei Yang; Jianbiao Huang; Dingyi Zhang; Yugen Li; Xiaoning Wang; Fengzhen Luo; Zhihua He (Frontiers in Surgery)
ObjectiveTo evaluate the feasibility, safety, and efficacy of local anesthesia applied to percutaneous nephrolithotomy (PCNL) under Enhanced Recovery After Surgery (ERAS) for treating upper urinary tract stones.Materials and methodsThis study was a prospective, single-center randomized controlled study in which the patients were randomly divided into two groups: 40 in the ERAS PCNL under local anesthesia (ERAS-LA) group and 40 in the ERAS PCNL under general anesthesia (ERAS-GA) group). The primary indicators were stone-free rate; the secondary outcomes were intraoperative and postoperative complications, intraoperative and postoperative VAS pain scores and postoperative stress response indicators. A meta-analysis was also performed using RevMan 5.4 software by searching relevant literatures in PubMed/Medline, Web of Science and Embase.ResultsThe stone clearance rates at 48 h were similar between the two groups [ERAS-LA: 85.0% (34/40) vs. ERAS-GA: 87.5% (35/40), P = 0.800] and both 90% at 1 month. The incidence of surgical complications was similar between the two group. The intraoperative pain score in ERAS-LA group was 2.90 ± 0.74, and the postoperative 24-h pain score was comparable between the two groups (ERAS-LA: 2.65 ± 1.35 vs. ERAS-GA: 2.63 ± 0.98, P = 0.925), with good pain control. The mean total operative time was lower in ERAS-LA group than in ERAS-GA group (68.15 ± 24.11 min vs. 82.125 ± 20.42 min, P = 0.006). Postoperative hemoglobin change values (3.38 ± 3.00 × 109/L vs. 5.22 ± 4.18 × 109/L, P = 0.027) and stress response factors including C-reactive protein (8.39 ± 7.46 mg/L vs. 10.47 ± 10.30 mg/L, P = 0.035) and interleukin-6 (5.40 ± 1.50 pg/ml vs. 10.57 ± 1.82 pg/ml, P = 0.041) were significantly lower in ERAS-LA group. The mean catheter retention, fistula retention, and postoperative hospital stay were all significantly lower in ERSA-LA group than in ERSA-GA group (2.3%, 2.9%, and 5.08 days vs. 3.33%, 4.38%, and 6.35 days, P < 0.05). The results of the meta-analysis were similar to that of our study.ConclusionsLocal anesthesia applied to ERAS-managed PCNL have a comparable stone clearance rates and complication rates, and a faster postoperative recovery, lower surgical stress, length of stay, anesthesia costs and hospital costs than general anesthesia.Clinical Trial Registrationhttp://www.medresman.org.cn, identifier (ChiCTR2100045681).